Axial Age, China and the meaning of Transcendence (The Macau Ricci Institute Journal, 2018)
The notion of an Axial Age shaped by Karl Jaspers after the World War II has been evaluated in various ways within the field of intellectual history, not only in the West but also in China: concretely can this concept be applied to Chinese tradition and if so, what does it mean in Chinese culture? Specialists on China in the West have different answers to these questions.Following the translation of Jaspers’ book into Chinese, several Chinese scholars have integrated this concept of an Axial Age in their reflections about Chinese Antiquity.This concept of an Axial Age matters because this concept affirms humanity’s universal openness to transcendence. However, because this notion was argued in a Western context, it always possesses the risk of projecting foreign constructions on Chinese tradition. From a Chinese perspective, it has to be reconstructed taking into consideration the specificities of Chinese tradition and the ways Chinese scholars speak about it, if it is to suggest a universal claim.